Design of Electrical Power Transfer Automation System Between PLN, PLTS and Genset Using Relay - Sunarto; Tri Nur Arifin (International Journal Science and Technology, 2025)
Electrical system use one single source are often vulnerable to disruptions, especially in area with unstable electricity supply. This study presents the development and implementation of an automation system for seamless power transfer management between three primary sources: PLN, PLTS and Genset. The primary objective of this system are to improve electricity supply, optimize renewable use energy, and reduce operational cost. Relay are used as crucial actuator to automatically switch between power source based on pre-set priority logic. When the PLN power source voltage range from 180.3 to 260.2 volt, the automation system immediately switch to the first backup power source, the PLTS, with a voltage range of 220.2 volt. When the PLN and PLTS voltage are 0 volt, the automation system switch to the second backup power source, the genset, with a voltage range of 220.2 volt. If the PLTS and Genset are 0 volt, the system will return to the primary priority source, the PLN, with a voltage range of 220.2 volt. Simulation test results show that the system is afford of detecting power availability and quality from each power source and automatically transitioning power with a fast response time. The implementation of relay ensures effective isolation and reliable switching control.